Perancangan Game Matching Card Untuk Meningkatkan Memori Otak Pada Anak - Nezahaidar Zein A (Informatics Engineering Department-UWKS, 2019)
Android-based smartphone mobile applications have many purposes aimed at their users. The difficulty of students remembering and understanding the material [1] This can have a positive effect on smartphone users who have low memory. This application development aims to develop android-based game applications that can be played, can be entertainment or spare time, can train memory skills, can make it easier to solve a problem and also increase the focus of the user [2]. Therefore, the design of educational games was made. Game Matching Card is a game first by using the randomization of the image first. Randomization of images in the game using yahoo fisher yates which later this application can be run on the android platform